Prison officer legitimacy, their exercise of power, and inmate rule breaking - Steiner, Benjamin (Criminology, 2018)
Prison officers are directly responsible for transmitting penal culture and prison policy to the confined, yet few studies of officers’ impact on inmate behavior have been conducted. We examined the effect of inmates’ perceptions of officer legitimacy on rule breaking within prisons, as well as the effects of officers’ reliance on different power bases on rates of rule breaking across prisons. The findings from bi‐level analyses of data from inmates and officers from 33 prisons revealed that inmates who held stronger views regarding officer legitimacy committed fewer nonviolent infractions but that perceived legitimacy did not affect the number of violent offenses inmates committed. We also examined a subsample of inmates encountered by officers for a rule violation and found no relationship between perceived legitimacy and subsequent rule breaking, although stronger perceptions of procedural justice related to the incident did directly and indirectly (through perceived legitimacy) coincide with lower odds of nonviolent misconduct. At the prison level, we found that prisons in which officers exercised their authority more lawfully and fairly (positional power) or by relying more on their skills and expertise (expert power) had lower rates of violent or nonviolent rule violations. Prisons in which officers relied more on coercion had higher levels of nonviolent infractions.